MANAGEMENT OF TOURIST AUTHORITY BASED ON PUBLIC-PRIVATE PARTNERSHIP (British Journal of Global Ecology and Sustainable Development, 2023)
The article developed scientific and practical recommendations and proposals to substantiate the tripartite approach of using the PPP mechanism to increase the tourism potential of the region, and also provides information on the tourism sector of the region in the Fergana region by years.